Corporate Social Responsibility and Executives’ Attitudes in Germany, Poland and Hungary - Bluhm, Katharina; Trappman, Vera (Warsaw Forum of Economic Sociology, 2015)
By examining executives’ cognitive concepts of responsibility and the CSR activities of companies in three latecomers to explicit Corporate Social Responsibility (CSR) - East and West Germany, Poland and Hungary - we show that the specific contexts matter for both. However, attitudes and activities are not in a deterministic relation. In (West) Germany, a neocorporatist concept of collective regulation is supportive of CSR, and implicit CSR is not driven out by an explicit CSR. In Poland and Hungary, the public discourse on CSR promoted by the EU has led to a ceremonial adoption of CSR by companies, while etatist and minimalist concepts of responsibility are relatively widespread. Substantive CSR is fostered by multinationals and executives who have studied in an Anglo-Saxon country. Yet, this seems not to be a peculiar feature of the Polish and Hungarian ’dependent market economy’.